2014
DOI: 10.5194/acp-14-2735-2014
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contributions of natural emissions to ozone and total fine PM concentrations in the Northern Hemisphere

Abstract: Abstract. Accurate estimates of emissions from natural sources are needed for reliable predictions of ozone and fine particulate matter (PM 2.5 ) using air quality models. In this study, the large-scale atmospheric chemistry transport model, DEHM (the Danish Eulerian Hemispheric Model) is further developed, evaluated and applied to study and quantify the contributions of natural emissions of VOCs, NO x , NH 3 , SO 2 , CH 4 , PM, CO and sea salt to the concentration of ozone and formation of PM 2.5 for the year… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 81 publications
(108 reference statements)
1
32
0
Order By: Relevance
“…Despite large changes in the emissions of ozone precursors and in net chemical production, the general location of these net production and loss regimes is thought to have changed little since pre-industrial times (Wild and Palmer, 2008). However, spatial heterogeneity of anthropogenic precursor emissions and of biogenic hydrocarbons (Zare et al, 2014), along with strong diurnal variability in chemical processes, deposition and meteorology, suggests that local ozone production and loss regimes in the boundary layer may be much more diverse than indicated by these coarse, regional-scale assessments.…”
Section: What Controls Ozone?mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite large changes in the emissions of ozone precursors and in net chemical production, the general location of these net production and loss regimes is thought to have changed little since pre-industrial times (Wild and Palmer, 2008). However, spatial heterogeneity of anthropogenic precursor emissions and of biogenic hydrocarbons (Zare et al, 2014), along with strong diurnal variability in chemical processes, deposition and meteorology, suggests that local ozone production and loss regimes in the boundary layer may be much more diverse than indicated by these coarse, regional-scale assessments.…”
Section: What Controls Ozone?mentioning
confidence: 99%
“…Archibald et al (2011) showed that there is a significant impact of mechanism uncertainties on the global impact of isoprene chemistry on ozone. Recent estimates from Zare et al (2014) found BVOC to be the most significant contributor to ozone formation over land areas in the Northern Hemisphere enhancing the mixing ratio by about 11 %. In the Pearl River Delta in China (Situ et al, 2013) ozone is sensitive to the BVOC levels particularly in urban areas.…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%
“…Because a substantial amount of ozone and ozone precursors are produced or emitted in Africa, tropospheric ozone in the other continents is largely influenced by ozone outflow from Africa (Williams 200 et al, 2009;Zare et al, 2014). American ozone that influences Asia mostly over high altitudes (north of 30N) (Wild et al, 2004;Holloway et al, 2008;Nagashima et al, 2010;Zhu et al, 2017b) (Wild et al, 2004;Sudo and Akimoto, 2007;Zhu et al, 2017b).…”
Section: Seasonal Variation In Imported African Ozone Over Asiamentioning
confidence: 99%
“…Consequently, the contribution of biogenic emissions to ozone in the African upper troposphere is larger than biomass burning and anthropogenic emissions (Aghedo et al, 2007;Zare et al, 2014 (Sauvage et al, 2005). From boreal winter to fall, biomass burning regions shift southward from central Africa to southern Africa (Fig.…”
Section: Seasonal Variation In Imported African Ozone Over Asiamentioning
confidence: 99%
“…Given the important role of natural emissions in the chemistry of the atmosphere (Zare et al, 2014), large-scale future tree mortality may influence ozone production and organic aerosol concentrations. Nonattainment of O 3 air quality standards in the US is more sensitive to BVOC emissions than anthropogenic VOC emissions (Hakami et al, 2006), and secondary organic aerosol mass can be dominated by biogenic sources (Pye et al, 2010).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%